2013
DOI: 10.1021/es303895w
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Carbadox Mediated by Reaction of Mn(III) with Oxalic Acid

Abstract: Manganese(III) geocomponents are commonly found in the soil environment, yet their roles in many biogeochemical processes remain unknown. In this study, we demonstrated that Mn(III) generated from the reaction of MnO(2) and oxalic acid caused rapid and extensive decompositions of a quinoxaline-di-N-oxide antibiotics, viz carbadox. The reaction occurred primarily at the quinoxaline-di-N-oxide moiety resulting in the removal of one -O from N1-oxide and formation of desoxycarbadox. The reaction rate was accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…As a strong one-electron transfer (acceptor or donor) oxidant (eqs and ), Mn­(III) is considered to play an important role in bio-geochemical process and water treatment. In nature, Mn­(III) can arise from direct dissolution of hausmannite or from interaction between pyrolusite or manganite with divalent manganese . It can also be produced by the oxidation of Mn­(II) using photooxidation, bacteria, enzyme, humic acid, and chemical agents (dissolved oxygen, Cr 2 O 7 2– , and so on) , or the reduction of permanganate or manganese dioxide (MnO 2 ) using oxalate, Mn 2+ , and other reductants. Nevertheless, free Mn­(III) is unstable and it can rapidly disproportionate to Mn 2+ and MnO 2 (eq ) because of its tetragonally distorted electron configuration . Most studies on the reaction of organic contaminants with Mn­(III) were focused on long-lived Mn­(III) species, including Mn­(III/IV) oxide, Mn­(III)-rich MnO 2 , and soluble Mn­(III) complexes with organic or inorganic ligands (such as citrate, oxalate, pyrophosphate (PP; eq ), ethylenediaminotetraacetate (EDTA), humic substances, and siderophores, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a strong one-electron transfer (acceptor or donor) oxidant (eqs and ), Mn­(III) is considered to play an important role in bio-geochemical process and water treatment. In nature, Mn­(III) can arise from direct dissolution of hausmannite or from interaction between pyrolusite or manganite with divalent manganese . It can also be produced by the oxidation of Mn­(II) using photooxidation, bacteria, enzyme, humic acid, and chemical agents (dissolved oxygen, Cr 2 O 7 2– , and so on) , or the reduction of permanganate or manganese dioxide (MnO 2 ) using oxalate, Mn 2+ , and other reductants. Nevertheless, free Mn­(III) is unstable and it can rapidly disproportionate to Mn 2+ and MnO 2 (eq ) because of its tetragonally distorted electron configuration . Most studies on the reaction of organic contaminants with Mn­(III) were focused on long-lived Mn­(III) species, including Mn­(III/IV) oxide, Mn­(III)-rich MnO 2 , and soluble Mn­(III) complexes with organic or inorganic ligands (such as citrate, oxalate, pyrophosphate (PP; eq ), ethylenediaminotetraacetate (EDTA), humic substances, and siderophores, etc.…”
Section: Introductionmentioning
confidence: 99%
“…68 Free aqueous Mn(III) is short-lived and undergoes disproportionation to soluble Mn(II) and solid Mn(IV) 21 but commonly occurs in environmental systems such as soils, 65 natural water bodies, 26 and sediments. 25 This is due to the formation of stable, water-soluble Mn(III) complexes with natural ligands, including pyrophosphate, 27 oxalate, 64 citrate, 69 and siderophores. 21 BPA Degradation by Oxidized Mn Species.…”
Section: ■ Discussionmentioning
confidence: 99%
“…MnO 2 polymorphs occur commonly in natural sediments, and 26–348 mg L –1 MnO 2 has been reported in freshwater sediments , and 2–16 mg L –1 in the surface layer of marine sediments . In addition to Mn­(IV), Mn­(III) is a strong oxidant, which has been recognized to play a role in biogeochemical cycling, and is an intermediate in biotic Mn­(II) oxidation, biotic MnO 2 reduction, and abiotic permanganate reduction . Free aqueous Mn­(III) is short-lived and undergoes disproportionation to soluble Mn­(II) and solid Mn­(IV) but commonly occurs in environmental systems such as soils, natural water bodies, and sediments .…”
Section: Discussionmentioning
confidence: 99%
“…Phenylarsonic acid compounds, primarily 4-aminophenylarsonic acid ( p -arsanilic acid, p -ASA) and 4-hydroxy-3-nitrophenylarsonic acid (roxarsone, ROX), have been widely used as feed additives in the intensive farming of poultry and swine for the purposes of enhancing feed conversion, controlling intestinal coccidiosis, and improving the color of hair and meat. , These compounds are added at rather high levels (typically 25–100 mg·kg –1 ) in swine and chicken feeds, while only a very small fraction of them are metabolically absorbed in the animal bodies . As a result, swine and poultry wastes often contain elevated levels of arsenic species, for example, animal manures in China have been reported to have total arsenic contents ranging from 1 to 70 mg·kg –1 . After storage in lagoons or composting, the animal manure, along with the phenylarsonic feed additives, is subsequently applied on farmlands as an organic fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…3 As a result, swine and poultry wastes often contain elevated levels of arsenic species, for example, animal manures in China have been reported to have total arsenic contents ranging from 1 to 70 mg•kg −1 . 4 After storage in lagoons or composting, the animal manure, along with the phenylarsonic feed additives, is subsequently applied on farmlands as an organic fertilizer. Analysis of 212 animal manure compost samples collected from 10 Chinese provinces with dense population and high livestock densities in 2014 showed that their arsenic contents varied from 0.37 to 71.7 mg• kg −1 .…”
Section: ■ Introductionmentioning
confidence: 99%